Religion and spirituality as a core module in social work education in Nigeria: perspectives of social work educators. Issue 4 (2nd October 2022) - Agbawodikeizu, Patricia U.; Levy, Susan; Ekoh, Prince Chiagozie; Chukwu, Ngozi Eucharia; Okoye, Uzoma Odera
ABSTRACT: Religion and spirituality are central to everyday life in Nigeria. Social work educators recognize that learning cannot be separated from the influence of context, including religion and spirituality. This study presents the first empirical inquiry into religion and spirituality in social work education in Nigeria. The qualitative study explored the inclusion of religion and spirituality on Nigerian social work programs from the viewpoints of social work educators, adopting a phenomenological approach. Data from key informants' semi-structured interviews with 12 purposively sampled social work educators based at three Nigerian universities (University of Nigeria, Nsukka; University of Benin, and Nnamdi Azikiwe University) were analyzed thematically. The findings highlight the importance of religion and spirituality in social work education; yet point to coverage being limited and located within elective modules, and for social work educators to recognize the relevance of religious and spiritual aspects of their students' and service users' existence in developing educational curricula. The study calls for prioritizing the integration of religion and spirituality in social work degree programs. Strengthening the links between religion, spirituality, and social work will better prepare future practitioners to be cultural component and work with the profession's values of social justice.